Solid electrolyte material, preparation method, electrode and lithium ion battery
By anionic doping of LZC chloride solid electrolyte, increasing the crystal structure disorder and broadening the Li+ transmission channel, the problems of halide solid electrolyte being unstable to low voltage negative electrodes and being unstable to air are solved, high ionic conductivity and improved chemical and thermal stability are achieved, and the performance of all-solid state batteries are improved.
Patent Information
- Application Number
- CN202411833225.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
AI Technical Summary
The halide solid electrolyte is unstable to the low-voltage negative electrode and cannot match the low-voltage negative electrode. It is also unstable to air and is prone to react with water in the air. It has low room temperature ionic conductivity, poor chemical stability and thermal stability, which hinders its further development in all-solid-state batteries.
By anion doping of LZC chloride solid electrolyte, the disorder of the crystal structure is increased, the Li+ transmission channel is broadened, and the ionic conductivity is improved. The specific method includes mechanical ball milling to synthesize the compound LixZrCl(4+x)-2(y+z)OySz represented by Formula 1 under an inert atmosphere, wherein 1.25≤x≤2.25, 0.5≤y≤2.25, and 0.05≤z≤0.35.
The ionic conductivity of the halide solid electrolyte is improved to about 3.2mS/cm, the chemical and thermal stability of the electrolyte is enhanced, the matching with the low-voltage negative electrode is improved, the risk of reaction with air is reduced, and the performance of all-solid state batteries is improved.
Smart Images

Figure CN119650826A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a solid electrolyte material, a preparation method, an electrode and a lithium ion battery. Background Art
[0002] Organic electrolytes in traditional lithium-ion batteries are usually flammable and fluid, volatile, flammable, and leaky, with certain safety risks. Therefore, using non-flammable, high elastic modulus solid electrolytes instead of organic liquid electrolytes to build all-solid-state lithium-ion batteries can not only avoid the safety hazards brought by organic liquid electrolytes, prevent dendrites from piercing the diaphragm and causing battery short circuits, solve battery safety issues, but also make metal lithium negative electrodes possible and increase battery energy density.
[0003] As the main component of all-solid-state batteries, solid electrolytes have a key impact on the electrochemical performance and cost of batteries. Among solid electrolytes, halide solid electrolytes are considered to be the most promising candidates for solid electrolytes in high-voltage all-solid-state lithium-ion batteries due to their high ionic conductivity, excellent high-voltage stability and good compatibility with electrode materials. For example, the low-cost lithium-ion conductor chloride solid electrolyte Li2ZrCl6 (LZC) belongs to the trigonal system, can remain stable at 4.2V, and has good compatibility with high-voltage positive electrode materials. However, halide solid electrolytes are unstable to low-voltage negative electrodes and cannot match low-voltage negative electrodes. At the same time, halide solid electrolytes are unstable to air and easily react with water in the air. They have relatively low room temperature ionic conductivity, poor chemical stability and thermal stability, which hinder their further development in all-solid-state batteries. Summary of the invention
[0004] Based on this, it is necessary to provide a solid electrolyte material, a preparation method, an electrode and a lithium ion battery for the above-mentioned technical problems existing in the prior art. The present invention increases the disorder of the crystal structure by anion doping of LZC chloride solid electrolyte, broadens the Li + The transmission channel improves the ionic conductivity, which can be increased to about 3.2mS / cm.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0006] A solid electrolyte material, comprising a compound represented by Formula 1,
[0007] Formula 1: Li x ZrCl (4+x)-2(y+z) O y S z ,
[0008] Wherein, in Formula 1, 1.25≤x≤2.25, 0.5≤y≤2.25, 0.05≤z≤0.35.
[0009] In a feasible implementation, y and z satisfy the following relationship:
[0010] Preferably, y and z satisfy the following relationship:
[0011] In order to solve the above technical problems, another technical solution adopted by the present invention is:
[0012] A method for preparing the solid electrolyte material as described above comprises the following steps:
[0013] S1. In a glove box, weigh LiCl, Li2O, Li2S and ZrCl4 in stoichiometric ratio and add them into a high-energy ball mill;
[0014] S2, placing the ball mill jar into a ball mill for mechanical ball milling to synthesize a compound represented by Formula 1,
[0015] Formula 1: Li x ZrCl (4+x)-2(y+z) O y S z ,
[0016] Wherein, in Formula 1, 1.25≤x≤2.25, 0.5≤y≤2.25, 0.05≤z≤0.35.
[0017] In a feasible implementation, both step S1 and step S2 are performed under an inert atmosphere.
[0018] In a feasible implementation, y and z satisfy the following relationship:
[0019] Preferably, y and z satisfy the following relationship:
[0020] In a feasible implementation, the inert atmosphere is argon, wherein the oxygen and water contents thereof are ≤0.01 ppm.
[0021] In a feasible implementation, the ball-to-material mass ratio in mechanical ball milling synthesis is (20-50):1, the diameter types of the ball milling beads used include 5mm, 8mm, and 10mm, and the ball milling beads are made of zirconia.
[0022] In a feasible implementation, the ball milling speed of the mechanical ball milling synthesis is 500-700 rpm, and the time is 40-60 hours.
[0023] In a feasible implementation, a pre-milling step is also included before the mechanical ball milling synthesis, in which the ball milling speed is 100-150 rpm and the time is 1-2 hours. The pre-milling step can refine the raw materials and mix the raw materials uniformly, thereby improving the reaction rate and product synthesis effect.
[0024] In order to solve the above technical problems, another technical solution adopted by the present invention is:
[0025] An electrode comprises the solid electrolyte material as described above or the solid electrolyte material prepared by the preparation method as described above.
[0026] In order to solve the above technical problems, another technical solution adopted by the present invention is:
[0027] A lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte comprises the solid electrolyte material as described above or the solid electrolyte material prepared by the preparation method as described above.
[0028] Due to the adoption of the above technical solution, the present invention has the following advantages compared with the prior art:
[0029] 1. The present invention can increase the disorder of the crystal structure and broaden the Li + The transmission channel improves the ionic conductivity, which can be increased to about 3.2mS / cm.
[0030] 2. After synthesis, the solid electrolyte material of the present invention can be directly assembled into a battery for use, and a high ionic conductivity electrolyte can be obtained without the need for a calcination step. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Graph showing the variation of ionic conductivity with oxygen-sulfur ratio in various embodiments of the present invention;
[0032] Figure 2 1 is an electrochemical impedance spectroscopy diagram of each embodiment of the present invention. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0035] At present, halide solid electrolytes are unstable to low-voltage negative electrodes and cannot match low-voltage negative electrodes. At the same time, halide solid electrolytes are unstable to air and easily react with water in the air. They also have relatively low room-temperature ionic conductivity, poor chemical stability and thermal stability, which hinder their further development in all-solid-state batteries.
[0036] On this basis, the present invention provides a solid electrolyte material, a preparation method, an electrode and a lithium ion battery. The present invention increases the disorder of the crystal structure and broadens the Li + The transmission channel improves the ionic conductivity, which can be increased to about 3.2mS / cm.
[0037] The specific doping mechanism is as follows: LZC oxygen doping greatly improves the amorphous degree of halide electrolytes, introduces an ion transport mechanism based on disordered local structures, reduces the restriction of anion frameworks in the crystalline structure on lithium ion transport, reduces the lithium ion transport barrier, and improves ion conductivity. Appropriate introduction of sulfur doping to replace some oxygen or halogen atoms forms new chemical bonds and structural defects, optimizes the amorphization degree of halides, reduces the lithium ion transport barrier, and further improves the halide ion conductivity. However, too high a proportion of S may lead to serious defects in the crystal structure and hinder lithium ion transport; too low a proportion of S and too high a proportion of O will also cause changes in the crystal structure, so the ratio of S to O needs to be controlled.
[0038] This embodiment provides a solid electrolyte material, including a compound represented by Formula 1,
[0039] Formula 1: Li x ZrCl (4+x)-2(y+z) O y S z ,
[0040] Among them, in Formula 1, 1.25≤x≤2.25, and can also be 1.50≤x≤2.15, 1.65≤x≤2.15, 1.85≤x≤2.15.
[0041] 0.5≤y≤2.25, can also be 0.5≤y≤2.15, 0.5≤y≤1.95, 0.5≤y≤1.65, 0.5≤y≤1.35.
[0042] 0.05≤z≤0.35, and can also be 0.05≤z≤0.27, 0.05≤z≤0.23, 0.05≤z≤0.19, and 0.05≤z≤0.16.
[0043] In a feasible implementation, y and z satisfy the following relationship: You can also
[0044] Preferably, it can also be
[0045] This embodiment also provides a method for preparing the solid electrolyte material as described above, comprising the following steps:
[0046] S1. In a glove box, weigh LiCl, Li2O, Li2S and ZrCl4 in stoichiometric ratio and add them into a high-energy ball mill;
[0047] S2, placing the ball mill jar into a ball mill for mechanical ball milling to synthesize a compound represented by Formula 1,
[0048] Formula 1: Li x ZrCl (4+x)-2(y+z) O y S z ,
[0049] Among them, in Formula 1, 1.25≤x≤2.25, and can also be 1.50≤x≤2.15, 1.65≤x≤2.15, 1.85≤x≤2.15.
[0050] 0.5≤y≤2.25, can also be 0.5≤y≤2.15, 0.5≤y≤1.95, 0.5≤y≤1.65, 0.5≤y≤1.35.
[0051] 0.05≤z≤0.35, and can also be 0.05≤z≤0.27, 0.05≤z≤0.23, 0.05≤z≤0.19, and 0.05≤z≤0.16.
[0052] In this embodiment, y and z satisfy the following relationship: You can also
[0053] Preferably, it can also be
[0054] In this embodiment, both step S1 and step S2 are performed under an inert atmosphere.
[0055] In this embodiment, the inert atmosphere is argon, and may also be an inert atmosphere such as nitrogen, in which the oxygen and water content is ≤0.01 ppm.
[0056] In a feasible implementation, the mass ratio of ball to material in mechanical ball milling synthesis is (20-50):1, and can also be (20-45):1, (20-40):1, (20-35):1, (20-30):1, (20-25):1, the diameter types of the ball milling beads used include 5mm, 8mm, and 10mm, and the ball milling beads are made of zirconia.
[0057] In this embodiment, the ball milling speed of mechanical ball milling synthesis is 500-700rpm, and can also be 500-680rpm, 500-640rpm, 500-610rpm, 500-580rpm, and the time is 40-60h, and can also be 40-55h, 40-52h, 40-49h, 40-46h.
[0058] In this embodiment, a pre-milling step is also included before the mechanical ball milling synthesis, and the ball milling speed in the pre-milling step is 100-150 rpm, and can also be 100-140 rpm, 100-132 rpm, 100-125 rpm, and the time is 1-2 hours, and can also be 1-1.8 hours, 1-1.6 hours, and 1-1.5 hours. The pre-milling step can refine the raw materials and make the raw materials evenly mixed, thereby improving the reaction rate and the product synthesis effect.
[0059] This embodiment also provides an electrode, which includes the solid electrolyte material as described above or the solid electrolyte material prepared by the preparation method as described above.
[0060] This embodiment also provides a lithium-ion battery, which includes a positive electrode, a negative electrode and an electrolyte, and the electrolyte includes the solid electrolyte material as described above or a solid electrolyte material prepared by the preparation method as described above.
[0061] The present invention is described in detail below with reference to specific embodiments.
[0062] Example 1
[0063] This embodiment provides a solid electrolyte material and a preparation method thereof. The preparation method comprises the following steps:
[0064] S1. Under argon atmosphere, the oxygen and water content is ≤0.01ppm. According to the element molar ratio n(Li):n(Zr):n(Cl):n(O):n(S)=2:1:4.7:0.55:0.1, a certain amount of LiCl, Li2O, Li2S and ZrCl4 are weighed in the glove box, and the O / S doping ratio is 0.55:0.1, i.e. 5.5. All the materials are added to the high-energy ball mill, and a certain mass ratio of ball milling beads is added to it. The ball mill is tightened to ensure an inert dry atmosphere in the jar. Among them, the ball-to-material mass ratio is 30:1, the diameter of the ball milling beads used is 8mm, and the ball milling beads are made of zirconium oxide.
[0065] S2. Under the same inert atmosphere as step S1, the ball mill is placed in a ball mill for mechanical ball milling to obtain the halide electrolyte material Li2ZrCl 4.7 O 0.55 S 0.1 .
[0066] First, a pre-milling step is performed, wherein the ball milling speed is 100-150 rpm and the time is 1 hour. The pre-milling step can refine the materials and make the materials evenly mixed, thereby improving the reaction rate and the product synthesis effect.
[0067] Then, ball milling was performed at a speed of 700 rpm and a running time of 40 h to prepare the halide electrolyte material Li2ZrCl 4.7 O 0.55 S 0.1 .
[0068] Example 2
[0069] The materials and preparation methods used in this embodiment are the same as those in embodiment 1. The only difference between the solid electrolyte material in this embodiment and that in embodiment 1 is that n(Li):n(Zr):n(Cl):n(O):n(S)=2:1:4.51:0.65:0.095, and the O / S doping ratio is 0.65:0.095, i.e. 6.8. Finally, the halide solid electrolyte material obtained is Li2ZrCl 4.51 O 0.65 S 0.095 .
[0070] Example 3
[0071] The materials and preparation methods used in this embodiment are the same as those in embodiment 1. The only difference between the solid electrolyte material in this embodiment and that in embodiment 1 is that n(Li):n(Zr):n(Cl):n(O):n(S)=2:1:4.425:0.7:0.0875, the O / S doping ratio is 0.7:0.0875, i.e. 8, and the halide solid electrolyte material obtained is Li2ZrCl 4.425 O0.7 S 0.0875 .
[0072] Example 4
[0073] The materials and preparation methods used in this embodiment are the same as those in embodiment 1. The only difference between the solid electrolyte material in this embodiment and that in embodiment 1 is that n(Li):n(Zr):n(Cl):n(O):n(S)=2:1:4.35:0.75:0.075, the O / S doping ratio is 0.75:0.075, i.e. 10, and the halide solid electrolyte material obtained is Li2ZrCl 4.35 O 0.75 S 0.075 .
[0074] Example 5
[0075] The materials and preparation methods used in this embodiment are the same as those in embodiment 1. The only difference between the solid electrolyte material in this embodiment and that in embodiment 1 is that n(Li):n(Zr):n(Cl):n(O):n(S)=2:1:4.315:0.78:0.0625, the O / S doping ratio is 0.78:0.0625, i.e. 12.5, and the halide solid electrolyte material obtained is Li2ZrCl 4.315 O 0.78 S 0.0625 .
[0076] Example 6
[0077] The materials and preparation methods used in this embodiment are the same as those in embodiment 1. The only difference between the solid electrolyte material in this embodiment and that in embodiment 1 is that n(Li):n(Zr):n(Cl):n(O):n(S)=2:1:4.3:0.8:0.05, and the O / S doping ratio is 0.8:0.05, i.e. 16. Finally, the halide solid electrolyte material obtained is Li2ZrCl 4.3 O 0.8 S 0.05 .
[0078] Comparative Example 1
[0079] The preparation method used in this comparative example is the same as that in Example 1. The only difference from the solid electrolyte material in Example 1 is that only O is doped, n(Li):n(Zr):n(Cl):n(O)=2:1:4.4:0.8, and the halide solid electrolyte material finally obtained is Li2ZrCl 4.4 O 0.8 .
[0080] Comparative Example 2
[0081] The preparation method used in this comparative example is the same as that in Example 1. The only difference from the solid electrolyte material in Example 1 is that only S is doped, n(Li):n(Zr):n(Cl):n(S)=2:1:5.8:0.1, and the halide solid electrolyte material finally obtained is Li2ZrCl 5.8 S 0.1 .
[0082] Comparative Example 3
[0083] The materials and preparation methods used in this comparative example are the same as those in Example 1. The only difference between the solid electrolyte material in this comparative example and that in Example 1 is that n(Li):n(Zr):n(Cl):n(O):n(S)=2:1:4.3:0.5:0.35, and the O / S doping ratio is 0.5:0.35, i.e. 1.43. Finally, the halide solid electrolyte material obtained is Li2ZrCl 4.3 O 0.5 S 0.35 .
[0084] The ionic conductivity and electrochemical impedance spectroscopy of the solid electrolyte materials prepared in each embodiment and comparative example were tested. The ionic conductivity of each embodiment varies with the oxygen-sulfur ratio as shown in the figure below: Figure 1 As shown, the electrochemical impedance spectra of each embodiment are as shown in Figure 2 The ionic conductivity of each embodiment and comparative example is shown in Table 1.
[0085] The ionic conductivity test method is as follows:
[0086] Under argon environment (water ≤ 0.01ppm, oxygen ≤ 0.01ppm), weigh 100mg ± 1mg of sample powder and pour it into the assembled half mold, and flatten and assemble the full mold. After adding insulation covers on the upper and lower parts of the full mold, put it into the outer metal frame and tighten the screws; pressurize the entire mold to 3T, tighten the screws again, maintain the pressure for 1min and then release the pressure, connect the electrochemical workstation EIS test, the test range: 100mHz ~ 7mHz; after the EIS (electrochemical impedance spectroscopy) test is completed, the test curve is fitted using Z-view software to obtain the impedance value R, and the mold is disassembled in the glove box to demold, and the thickness L of the powder after tableting is tested; calculate the ionic conductivity σ = L / (R*S), the unit is mS / cm, where S is calculated from the mold diameter φ10.
[0087] Table 1 is a table of ionic conductivity of various embodiments and comparative examples.
[0088] sample Ionic conductivity (mS / cm) Example 1 2.281 Example 2 2.513 Example 3 3.24 Example 4 2.588 Example 5 2.501 Example 6 2.399 Comparative Example 1 2.048 Comparative Example 2 1.514 Comparative Example 3 1.46
[0089] As shown in Table 1, the ionic conductivity of Examples 1 to 3 increases with the increase of the oxygen-sulfur ratio, so that the battery has a fast ion transfer speed and small energy loss during the charge and discharge process, which improves the charge and discharge efficiency and stability of the battery. Batteries with high ionic conductivity have lower internal resistance, can reduce energy loss during charge and discharge, and improve battery efficiency and cycle life; and when the oxygen-sulfur ratio increases to a certain extent, that is, Examples 4 to 6, the ionic conductivity decreases with the increase of the oxygen-sulfur ratio. It can be seen from Comparative Examples 1 and 2 that the ionic conductivity of only doping O or only doping S is not as strong as that of O / S co-doping. It can be seen from Comparative Example 3 that when the O / S co-doping ratio is too low, the ionic conductivity is low and the overall performance of the battery will decrease.
[0090] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0091] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A solid electrolyte material, characterized in that: including a compound represented by Formula 1, Formula 1: Li x ZrCl (4+x)-2(y+z) About y S z , Wherein, in Formula 1, 1.25≤x≤2.25, 0.5≤y≤2.25, 0.05≤z≤0.
35.
2. The solid electrolyte material according to claim 1, characterized in that The y and z satisfy the following relationship: Preferably, y and z satisfy the following relationship:
3. A method for preparing a solid electrolyte material according to any one of claims 1 to 2, characterized in that: The steps include: S1. In a glove box, weigh LiCl, Li2O, Li2S and ZrCl4 in stoichiometric ratio and add them into a high-energy ball mill; S2, placing the ball mill jar into a ball mill for mechanical ball milling to synthesize a compound represented by Formula 1, Formula 1: Li x ZrCl (4+x)-2(y+z) About y S z , Wherein, in Formula 1, 1.25≤x≤2.25, 0.5≤y≤2.25, 0.05≤z≤0.
35.
4. The method for preparing a solid electrolyte material according to claim 3, characterized in that: Both step S1 and step S2 are performed under an inert atmosphere.
5. The method for preparing a solid electrolyte material according to claims 3 to 4, characterized in that: The inert atmosphere is argon, and the oxygen and water contents therein are ≤0.01 ppm.
6. The method for preparing a solid electrolyte material according to claim 3, characterized in that: The ball-to-material mass ratio in the mechanical ball milling synthesis is (20-50):1, the diameter types of the ball milling beads used include 5mm, 8mm, and 10mm, and the ball milling beads are made of zirconia.
7. The method for preparing a solid electrolyte material according to claim 3, characterized in that: The mechanical ball milling synthesis has a ball milling speed of 500 to 700 rpm and a time of 40 to 60 hours.
8. The method for preparing a solid electrolyte material according to claim 7, characterized in that: The mechanical ball milling synthesis also includes a pre-ball milling step, in which the ball milling speed is 100-150 rpm and the time is 1-2 hours.
9. An electrode, characterized in that: The electrode comprises the solid electrolyte material according to any one of claims 1 to 2 or a solid electrolyte material prepared by the preparation method according to any one of claims 3 to 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte comprises the solid electrolyte material according to any one of claims 1 to 2 or a solid electrolyte material prepared by the preparation method according to any one of claims 3 to 8.